Mild-temperature gasification of biomass as a carbon-neutral CO2 utilisation process - Michael J. Greencorn; S. David Jackson; Justin S.J. Hargreaves; Souvik Datta; Manosh C. Paul (Journal of CO2 Utilization)
Applying CO2 as a gasifying agent for renewable biomass feedstocks represents an innovative method of carbon dioxide utilisation (CDU) that could be carbon neutral. This effect has now been observed under low gasification temperatures of 600℃. When supplied at concentrations of 58.5 %v in a gasifying agent mixture with argon, CO2 was consumed in the resulting reaction and used to gasify char while producing excess syngas CO. This indicates a concentration-based push to drive CO2 utilisation reactions is possible at mild-temperatures, but net-CO2 conversion was limited to 0.434 % under these conditions. Conversion was highest during the period of char reduction following pyrolysis, indicating the principal route of conversion is the reverse Boudouard reaction. Mild-temperature CO2 gasification yielded an excess of 0.80 mmol/g of CO while generating 0.353 mmol/g less char-carbon than comparable pyrolysis experiments, further demonstrating the reverse Boudouard CO2-char conversion mechanism is active under these conditions. The CO2 gasifying agent does not appear to change the onset of pyrolytic devolatilization processes, although minor char-CO2 interactions are observed during pyrolysis as char is formed. Additionally, the CO2 atmosphere yielded 2.642 mmol/g more CH4 during devolatilization compared to pyrolysis under an inert atmosphere. These results are further discussed in the context of gasifier and system design parameters that maximise the thermal efficiency of integrated biomass power and BECCS (bioenergy with carbon capture and storage) cycles.